2021
DOI: 10.1002/advs.202004250
|View full text |Cite
|
Sign up to set email alerts
|

From Snapshots to Development: Identifying the Gaps in the Development of Stem Cell‐based Embryo Models along the Embryonic Timeline

Abstract: In recent years, stem cell-based models that reconstruct mouse and human embryogenesis have gained significant traction due to their near-physiological similarity to natural embryos. Embryo models can be generated in large numbers, provide accessibility to a variety of experimental tools such as genetic and chemical manipulation, and confer compatibility with automated readouts, which permits exciting experimental avenues for exploring the genetic and molecular principles of self-organization, development, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 197 publications
(309 reference statements)
0
4
0
Order By: Relevance
“…Moreover, Li et al observed that these structures recapitulated post-implantation polarization events on the molecular level ( Li et al, 2019 ). Importantly, however, current 2D in vitro culture methods for post-implantation morphogenesis of blastocysts and blastoids do not readily permit the formation of mural trophectoderm, associated parietal endoderm and the ectoplacental cone [current gaps in embryo model development are reviewed in Shankar et al (2021) ].…”
Section: Comparison Of Blastoids With Blastocystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Li et al observed that these structures recapitulated post-implantation polarization events on the molecular level ( Li et al, 2019 ). Importantly, however, current 2D in vitro culture methods for post-implantation morphogenesis of blastocysts and blastoids do not readily permit the formation of mural trophectoderm, associated parietal endoderm and the ectoplacental cone [current gaps in embryo model development are reviewed in Shankar et al (2021) ].…”
Section: Comparison Of Blastoids With Blastocystsmentioning
confidence: 99%
“…There can be little doubt that blastoids are a valuable addition to the collection of stem cell-based models. Compared to other stem cell-based embryo-like structures, including gastruloids, 2D micropatterned stem cells, post-implantation amniotic sac embryoids and embryonic-extraembryonic fusion embryoids [reviewed in Fu et al (2021) , Shankar et al (2021) ], blastoids have the unique potential to recapitulate the pre-implantation embryo and are therefore the singular model for studying this early stage of development in vitro.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Typically, embryo models, including blastoids, [ 2 ] extraembryonic/embryonic peri‐implantation models, [ 3 ] and gastruloids, [ 4 ] are formed by coaxing stem cells within a non‐adhesive (micro‐) environment that supports their unrestricted self‐organization potential. [ 2c,5 ] Embryo models are capable of recapitulating sequences of developmental processes, [ 6 ] modeling developmental defects, [ 6c,7 ] and providing insights into the molecular regulators driving development. [ 2a,e,8 ] Moreover, they have the potential to reveal hidden complexities in embryo morphogenesis and the assemblage of cell lineages at various stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances in micro‐engineering platforms and image‐based analysis software have enabled researchers to realize some potential applications of clinical and pharmaceutical research using embryo models. [ 5d,17 ] 3D high‐content phenotypic screening requires a versatile platform to allow long‐term culture, imaging, and quantification; robust culture conditions to allow reproducibility; simple and efficient read‐out, and supervised analysis to extract the most reliable information. [ 18 ] Soluble factors or compounds’ screening can serve as a powerful tool to study the function of signaling pathways in development.…”
Section: Introductionmentioning
confidence: 99%